2021
DOI: 10.3389/fnut.2021.731466
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Albumin-Globulin Score and Sarcopenia to Predict Prognosis in Patients With Renal Cell Carcinoma Undergoing Laparoscopic Nephrectomy

Abstract: We conducted a multicenter clinical study to construct a novel index based on a combination of albumin-globulin score and sarcopenia (CAS) that can comprehensively reflect patients' nutritional and inflammatory status and assess the prognostic value of CAS in renal cell carcinoma (RCC) patients. Between 2014 and 2019, 443 patients from 3 centers who underwent nephrectomy were collected (343 in the training set and 100 in the test set). Kaplan-Meier curves were employed to analyze the impact of albumin-globulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…A meta-analysis showed that patients with sarcopenia had worse OS (HR = 1.76; 95% CI, 1.35–2.31; P < 0.001). In addition, our previous studies confirmed that sarcopenia was an independent prognostic risk factor for patients with RCC ( 16 , 17 , 28 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A meta-analysis showed that patients with sarcopenia had worse OS (HR = 1.76; 95% CI, 1.35–2.31; P < 0.001). In addition, our previous studies confirmed that sarcopenia was an independent prognostic risk factor for patients with RCC ( 16 , 17 , 28 ).…”
Section: Discussionsupporting
confidence: 65%
“…A growing number of studies have shown that sarcopenia is associated with poor prognosis in oncology patients and is even an independent risk factor for prognosis ( 14 , 15 ). Our previous study found sarcopenia assessed by preoperative SMI measurements to be an independent risk factor for RCC patients ( 16 , 17 ). However, muscle mass, nutrition and inflammatory status may differ preoperatively and postoperatively due to primary tumor eradication, and major surgery can affect the physical condition of patients ( 18 ).…”
Section: Introductionmentioning
confidence: 98%
“…According to previous publications, A/G was independently associated with various cancers, such as lung cancer, squamous cell carcinoma of the maxillary sinus, diffuse large B cell lymphoma, and metastatic gastric cancer. These studies concluded that cancer patients with a low A/G had a worse overall and disease-free survival rate than those with a higher A/G ( 9 , 14 17 ). The present study indicated that patients with a lower A/G (A/G ≤ 1.09) had a higher SAP risk, while those with a higher A/G (A/G ≥ 1.4) had a lower risk.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the HRs extracted from the survival curve and univariate analysis may be not accurate as a matter of fact. Sixth, other than PNI, there are also other scores that are just as easy to use for prognosis prediction of RCC patients (e.g., Glasgow Prognostic Score [52][53][54], systemic immune-inflammation index [55], albumin-globulin score [56], platelet index score [57], et al). It may be necessary to determine which prognostic factor may be more accuracy [39] or whether different score systems should be integrated [56,58].…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, other than PNI, there are also other scores that are just as easy to use for prognosis prediction of RCC patients (e.g., Glasgow Prognostic Score [52][53][54], systemic immune-inflammation index [55], albumin-globulin score [56], platelet index score [57], et al). It may be necessary to determine which prognostic factor may be more accuracy [39] or whether different score systems should be integrated [56,58]. In summary, the prognostic and clinical values of pretreatment PNI in RCC still need to be confirmed by prospective large-scale studies which involve patients from various geographic areas and perform the comparison with other factors in the future.…”
Section: Discussionmentioning
confidence: 99%